Resilience mediates the influence of hope, optimism, social support, and stress on anxiety severity among Chinese patients with cervical spondylosis - Chu, Yuying; Zhang, Yuqiang; Wang, Suyan; Dai, Hongliang (Frontiers in Psychiatry, 2022)
Objective: Cervical spondylosis (CS) is a potential stressor threatening mental health among affected individuals. This study was to analyze resilience level and associated factors among cervical spondylosis (CS) patients, and to explore the underlying mechanism of anxiety based on resilience-focused psychological variables. Methods: Resilience Scale-14 (RS-14), Zung Self-Rating Anxiety Scale (SAS), Herth Hope Index (HHI), Revised Life Orientation Test (LOT-R), Multidimensional Scale of Perceived Social Support (MSPSS), Perceived Stress Scale-10 (PSS-10) were used in this cross-sectional investigation among 250 CS patients. Results: The score of resilience was 65.58 ± 16.14. Hierarchical linear regression analysis revealed that hope, optimism, perceived social support, perceived stress, and whether having comorbid chronic diseases were the independent associates of resilience among CS patients, which explained 63.9% of the total variance. The structural equation model showed that hope, optimism, perceived social support and perceived stress affected anxiety via resilience, and hope and optimism also had direct effects on anxiety. Conclusion: Chinese patients with CS had moderate level of mental resilience, which was independently related to hope, optimism, perceived social support, perceived stress, and whether having comorbid chronic diseases. Resilience played a mediating role between various psychological variables and anxiety. Improving the level of resilience, hope, optimism and perceived social support and reducing the level of perceived stress are important strategies to reduce anxiety level. Relevant healthcare professionals should put more focus on the mental problems of Chinese CS patients and help maintain good psychological status by improving their resilience and associated psychological variables thereof.